Ant Colony Optimization algorithm for determining the shortest routes to reduce distribution costs - Muharni, Yusraini; Febianti, Evi; Adipradana, Febby Chandra; Ilhami, Muhammad Adha; Muttaqin, Ade Irman Saeful; Kulsum, Kulsum; Herlina, Lely; Wulandari, Anting; Hartono, Hartono (Journal Industrial Servicess, 2023)
Distribution is an important activity that companies need to pay attention to. Improper planning for distribution activities can potentially waste both cost and time. Determining the shortest distribution route could help companies effectively reduce distribution costs. This research was conducted on a small and medium enterprise (SME) located in Rangkasbitung, Indonesia that sells various types of bread. Distribution activities carried out by Jaya Roti were found to be still conventional, while the distribution carried out to the city of Serang has many locations and complex route combinations. This research utilized the metaheuristic method of Ant Colony Optimization (ACO) with MATLAB software to determine the shortest route, which is included in the Travel Salesman Problem (TSP). The result of the shortest route determination was a total distance of 93,484 Km with an efficiency rate of 26.97% and a resulting cost of IDR 170,795.